Herd dynamics around the Russo-Ukraine war and Covid-19 pandemic - Mohamad, Azhar (2023)
This paper scrutinises the herding behaviour in commodity markets surrounding the Russo-Ukraine war and Covid-19 pandemic. Utilising both static and time-varying measures, we examine the herding intensity within the following commodity sectors: energy, metal, livestock and grain commodities. We document heterogeneity. The static measure uncovers no herding surrounding the Russo-Ukraine war, and very weak herding within the livestock commodity sector before the pandemic. Contrarily, while the time-varying measure indicates mild herding surrounding the war, it detects considerably stronger herding intensity, particularly within the energy and livestock commodities, during the pandemic. In summary, the war in Ukraine does not result in a strong herding pattern in the commodity markets relative to that during the pandemic – which signals that not all crises produce similar herding intensity.